2022
DOI: 10.1038/s41598-022-12708-1
|View full text |Cite
|
Sign up to set email alerts
|

A benchmark study on economic impact of Neem Coated Urea on Indian agriculture

Abstract: The policy of mandatory production and distribution of Neem Coated Urea (NCU) was implemented by the Government of India since 2015. In this article, authors have made an attempt to explore the benefits of NCU recognized by the producers of six major crops such as paddy, maize, sugarcane, tur, jute and soybean across six major states viz., Karnataka, Maharashtra, Madhya Pradesh, Bihar, Punjab and Assam. The results reveal that NCU use has contributed positively in terms of increasing the yield levels of main p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The share of (N+P+K) consumption declined from 57 per cent in the 1960s to 43 per cent in the 1970s, further to about 24.8 per cent in the 1980s, 21.3 percent in the 1990s before increasing to 26.2 per cent in 2000s. Almost a similar trend was observed in the case of nitrogenous and phosphatic fertilizers [20,21].…”
Section: Consumption Growth Rate Of Major Fertilizer In Indiasupporting
confidence: 79%
See 1 more Smart Citation
“…The share of (N+P+K) consumption declined from 57 per cent in the 1960s to 43 per cent in the 1970s, further to about 24.8 per cent in the 1980s, 21.3 percent in the 1990s before increasing to 26.2 per cent in 2000s. Almost a similar trend was observed in the case of nitrogenous and phosphatic fertilizers [20,21].…”
Section: Consumption Growth Rate Of Major Fertilizer In Indiasupporting
confidence: 79%
“…In this connection, the researchers came up with the development of Neem-Coated Urea (NCU), which helps increase Nitrogen Use Efficiency (NUE) in crops. Recognizing the potential benefits associated with NCU relative to NU, the Ministry of Agriculture and Farmers Welfare (MoA & FW), Government of India, included NCU in the Fertilizer Control Order (FCO) since July 2004 and subsequently made the production and distribution of NCU mandatory from 25 th May 2015 [20,19].…”
Section: Impact Of Neem-coated Urea On Total Fertilizer Consumptionmentioning
confidence: 99%
“…For example, the Indian Neem-coated urea initiative (Pathak 2023), could impact NH 3 emissions. However, current research observed no emissions reduction but improved crop yields (Ramappa et al 2022), underscoring the importance of assessing its positive and negative long-term effects on agriculture and the environment (Bhatia et al 2023). Without a region-based understanding of agricultural practices as they impact and are impacted by air pollution, our ability to make sound policies under a changing climate and growing food demand will be limited.…”
Section: Holistic Understanding Of Air Pollution-agriculture Linkagesmentioning
confidence: 95%
“…They further showed that CRNF decreased the cumulative NH 3 volatilization for early-and late-season rice by 20-43% and 20-32%, respectively, as compared with the conventional urea (Table 4). Neem-coated urea (NCU) is very popular in India and is garnering continuous attention from scientific communities across the world (Ramappa et al, 2022). Sireesha et al (2020) reported that 100% of NCU increased NUE (32.59 %) when compared with 100% of prilled urea (20.68 %).…”
Section: Controlled-release N Fertilizermentioning
confidence: 99%